The Effect of Online Tracking Systems and Timing Accuracy on Customer Loyalty Through Customer Satisfaction at J&T Express 2024 - Darmawan Apriyadi; Sarovah Widiawati; Nurul Nurul; Rosmallini Putri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to determine the effect of the online tracking system and time accuracy on customer loyalty through customer satisfaction at J&T Express East Jakarta 2024. This research used quantitative methods and nonprobability sampling techniques. To collect the data, the researchers used a questionnaire from J&T Express users which were then analyzed using the SEM-PLS (Structural Equation Modeling-Partial Least Square) method with SmartPLS 4.0 software. This study used the questionnaire data as a Likert scale that was assessed for validity and reliability. This research indicates that the online tracking system positively and significantly affects customer satisfaction. Delivery timing also has a positive and significant effect on customer satisfaction. In turn, customer satisfaction positively and significantly effects customer loyalty. The online tracking system positively and significantly effects customer loyalty through customer satisfaction. Time accuracy also positively and significantly effects customer loyalty through customer satisfaction.